The degree of using E-Learning websites by Jordanian universities’ student and Its relationship with quality assurance standards from the perspective of Quality Assurance Reprehensive - Bni Oudeh, Ahmad Rasheed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of using E-Learning websites by Jordanian universities’ student and its relationship with the comprehensive quality standards from the perspective of quality representatives in these universities. To achieve the objective of the study, the researcher used the descriptive correlation method and developed two tools. The first questionnaire examined the degree of using e-learning websites by Jordanian universities’ students and it consisted of (15) items. Where the second questionnaire, which examined the degree of applying the comprehensive quality standards, consisted of seven fields that cover (50) items. The validity and reliability of the two instruments were ascertained. The study sample consisted of (177) quality representatives from sixteen private and public universities located in the central district of the kingdom. The results of the study showed the following: The degree of using E-learning websites by Jordanian universities’ students was moderate (M=3.53), The degree of implementing E-learning quality assurance standards was high (M=3.71), and there is a positive correlation relationship with statistical significance at the level of significance (α=0.50) between the degree of using E-learning websites by Jordanian universities’ students and the implementation of E-learning quality assurance standards. The study recommended emphasizing the importance of applying quality standards as they have a significant role in improving the degree of students' use of e-learning sites.
Keywords: Comprehensive Quality; E-learning; Universities’ Students; Quality representative